Testing Samples of Three Independent Groups - Froncek, D. (Radioengineering Society, 1995)
A method of testing triples consisting of samples of three independent groups such that no two samples of the same group are tested at the same time, no sample is tested with another one more than once and after each test one sample of the triple is included in the following triple is presented.
Keywords: noise figure; noise parameters; noise matching